Os governos municipais conversam com o cidadão? Um olhar para as políticas públicas de informação e comunicação pela via dos portais da internet dos Municípios do Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
This thesis aimed to investigate whether the Municipalities of the State of Paraná with more than ten thousand inhabitants, would be using the potential of access to information and public communication in their Internet portals in order to encourage the increase of citizen participation in management. The preliminary hypothesis that guided the research is that the procedures for building public portals, that is, policies that guide access to information, are focused on a fiscal and anti-corruption view, while the procedures that guide the communication of the government are still focused on promoting the administration's image and protecting the ruler. They are distinct logics and none of them actually lends itself to improving social capital and reflecting on citizenship and democratic participation. Municipal government portals can serve as tools for access to information, transparency and good governance (e-Gov), offering facilities for viewing expenditures, facilitating access to services and increasing collection, as well as serving the policies of communication and e-democracy, making possible, in theory, greater participation of the citizen in the decisions that affect the lives of all. From Habermas' theory of communicative action and the proposal of dialogic communication and awareness in the form proposed by Paulo Freire, it is verified that it is necessary to promote access to information and communication in order to foster interest in participation, which can potentially improve the relationship of political agents with society and from this an increase in political culture and the legitimacy of decisions. The study analyzed the Portals of the Municipalities of the State of Paraná, observing the information about the actions and programs of the government in the areas of health, education and social assistance, housing and security, besides other elements that could contribute to the improvement of quality and the preliminary hypothesis, demonstrating that it is necessary to rethink the importance of the development of communication policies and the information policies, which do not only lend themselves to fiscal transparency, but actions to promote the increase of citizenship.
Keywords: Políticas de informação; Políticas de comunicação; Portais municipais; Cidadania; Policies of information; Policies of communication; Portals of the Municipalities; Citizenship; CNPQ::CIENCIAS SOCIAIS APLICADAS